2022
DOI: 10.3233/npm-221015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short-term outcomes of 35-weeks’ gestation infants cared for in a level II NICU vs mother-baby, a retrospective study

Abstract: BACKGROUND: Late preterm infants are at high risk for medical complications and represent a growing NICU population. While 34-weeks’ gestation infants are generally admitted to the NICU and 36-weeks’gestation infants stay in mother-baby, there is wide practice variation for 35-weeks’gestation infants. The objective of this study was to compare short-term outcomes of 35-weeks’ gestation infants born at two hospitals within the same health system (DUHS), where one (DRH) admits all 35-weeks’ gestation infants to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The studies included in this systematic review highlight potential characteristics contributing to increased readmission rates in LPT infants. The studies took place across the United States and internationally in Croatia, Canada, South Korea, Turkey, and England (Aliaga et al, 2014; Amsalu et al, 2022; Celik et al, 2013; Hwang et al, 2013; Isayama et al, 2020; Jang & Ju, 2020; Kardum et al, 2022; Moyer et al, 2014; Speer et al, 2021; Weimer et al, 2022; Young et al, 2013). Most of the studies were multicenter studies including two or more centers.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies included in this systematic review highlight potential characteristics contributing to increased readmission rates in LPT infants. The studies took place across the United States and internationally in Croatia, Canada, South Korea, Turkey, and England (Aliaga et al, 2014; Amsalu et al, 2022; Celik et al, 2013; Hwang et al, 2013; Isayama et al, 2020; Jang & Ju, 2020; Kardum et al, 2022; Moyer et al, 2014; Speer et al, 2021; Weimer et al, 2022; Young et al, 2013). Most of the studies were multicenter studies including two or more centers.…”
Section: Resultsmentioning
confidence: 99%
“…All of the studies that reviewed readmission of LPT infants did so during the first 28–30 days of life. Most of the studies examined LOS and its impact on readmission rates, which showed an inverse relationship with increased readmission rates (Aliaga et al, 2014; Celik et al, 2013; Moyer et al, 2014; Weimer et al, 2022; Young et al, 2013). Length of stay was increased with cesarean birth versus vaginal birth among LPT infants in the study by Hwang et al (2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations